ANALISIS PENGARUH OPERATING LEVERAGE , FINANCIAL LEVERAGE, DAN LIQUIDITY TERHADAP RENTABILITAS PERUSAHAAN DIBIDANG PERTANIAN YANG TERDAFTAR DI BEI (Tahun 2011-2015) - NOVIARTI (Pasca Sarjana Universitas Satya Negara Indonesia, 2016)
The purpose of this study was to determine the effect of Operating Leverage, Financial Leverage and Liquidity partially and simultaneously to profitability. The data used in this research is secondary data obtained from IDX is the company's financial statements from 2011-2015. The sample in this study is the Agricultural sector companies listed on the Indonesia Stock Exchange. This research applies multiple linear regression analysis using SPSS 23 (Statistics Package for the Social Sciences) for Windows. Results of the analysis showed that adjusted determination coefficient (adjusted R-square) of 0.2704 or 27.04%. Based on t test Operating Leverage is known that partially negatively affect the company's profitability in the agricultural sector, this is evide nced by the t test showed a smaller significance level of 0.05 is 0.003. T test also showed that financial leverage is partially not affect the company's profitability in the agricultural sector, this is evidenced by the t test showed significance level greater than 0.05 is 0.096. Liquidity, and a positive significant effect on the profitability of companies in the agricultural sector in the years 2011-2015 BEI. Based on hypothesis testing table 0095 t-test with significance 0.025 <0.05.Hal means Liquidity significant effect on profitability and acceptable hypothesis.